Hubungan Sumber Informasi Terhadap Pengetahuan Dan Sikap Masyarakat Tentang Penyakit Menular Seksual di Desa Pukdale Kecamatan Kupang Timur - Ermi Lilianda Alang; Diah Ayu Dwi Satiti; Ninick Corea Fernandez (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Reproductive health is complete physical, mental and social well-being in all matters relating to reproductive systems and functions and processes and not just conditions that are free from disease and disability. One of the reproductive health problems that we are often familiar with is sexually transmitted infections. Sexually Transmitted Infections (STI) are infectious diseases that are transmitted mainly through sexual contact, and are currently still a public health problem throughout the world, both in developed (Industrial) countries and in developing countries. Research Objective: To determine the effect of health promotion about STI (Sexually Transmitted Infections) on community knowledge, in this case teenagers in Pukdale Village, East Kupang District. Research Method: This type of research uses the Quasi Experiment One Group Pre Test-Post Test method, using the Wilcoxon analysis test. This research was conducted in October 2023. Using a total sampling of 45 respondents as samples. The questionnaire used consisted of 20 statement items. Results: The relationship between health promotion and adolescent knowledge of sexually transmitted infections, before health promotion regarding STIs was carried out, 2 respondents (4.4%) had good knowledge, 14 respondents (31.3%) had sufficient knowledge, and 29 respondents (64.4%) had good knowledge. less and after health promotion regarding STIs was carried out, 17 respondents (37.8%) had good knowledge, 20 respondents (44.4%) had sufficient knowledge, and 8 respondents (17.8%) had poor knowledge. The relationship results use the correlation test ρ = 0.000 < 0.05. Conclusion: There is a significant relationship between health promotion and public knowledge, in this case teenagers, regarding Sexually Transmitted Infections after health promotion is carried out.